Odpowiedzi

2010-02-25T08:19:00+01:00
4x=6y/:4
x=3/2
⅔x+½y=⅓
⅔ *3/2 + ½y=⅓
1+½y=⅓
½y=⅓-1
½y=-⅔/*2
y=-4/3
x=3/2= 1 ½, a y=-4/3= -1 ⅓
1 1 1
Najlepsza Odpowiedź!
2010-02-25T08:21:50+01:00
4x-6y=0/*(-1)
⅔x+½y=⅓/*6

{-4x+6y=0
+ {4x+3y=2
-------------------
9y=2/:9
y=2/9


4x-6y=0
4x=0+6y
4x=6 * 2/9
4x=4/3/:4
x=⅓

x=⅓
y=2/9



5 3 5
2010-02-25T08:23:42+01:00
4x-6y=0
⅔x+½y=⅓

4x=6y /:4
⅔x+½y=⅓

x=3/2y
2/3*3/2y+1/2y=1/3

x=3/2y
6/6y+3/6y=1/3

x=3/2y
3/2y=1/3 /:3/2

x=3/2y
y=2/9

x=3/2*2/9
y=2/9

x=3/9
y=2/9
Spr:
4x-6y=0
⅔x+½y=⅓
4*3/9-6*2/9=0
2/3*3/9+1/2*2/9=1/3
12/9-12/9=0
6/27+2/18=1/3
0=0
12/54+6/54=1/3
18/54=1/3
1/3=1/3
2 3 2